A novel NSDHL variant in CHILD syndrome with gastrointestinal manifestations and localized skin involvement. Issue 1 (26th December 2021) - Tan, Ene‐Choo; Chia, Shi Yun; Rafi'ee, Khadijah; Lee, Shan Xian; Kwek, Andrew Boon Eu; Tan, Sze Hwa; Ng, Victor Weng Leong; Wei, Heming; Koo, Stephanie; Koh, Ai Ling; Koh, Mark Jean‐Aan
Abstract: Background: CHILD syndrome is an X‐linked dominant disorder associated with pathogenic mutations in the NSDHL gene. The condition is predominantly found in females as it is lethal in males. Most cases present at birth with extensive unilateral ichthyosiform erythroderma involving the trunk and limbs. Milder and less extensive presentations have been reported, leading to misdiagnosis especially during early childhood. Methods and Results: We report an adult female of Malay ancestry who presented with minimal skin and limb involvement. She was only diagnosed in adulthood when she presented with gastrointestinal symptoms and worsening of skin manifestations. The clinical diagnosis was suspected after a combination of clinical, pathological and immunohistochemistry correlation, and molecularly confirmed with the discovery of a frameshift variant in NSDHL . The novel variant was inherited from her mother who had some linear hypopigmented patches over the medial aspects of both her arms and right forearm. Conclusion: We uncovered a novel frameshift variant associated with presentations that cast a new light on the clinical features of CHILD syndrome. Abstract : A novel NSDHL frameshift variant in a patient with subtle skin features and almost no limb defects, with gastrointestinal symptoms and presence of multiple whitish plaques in the proximal duodenum, stomach and distal oesophagus.